A Multidimensional Evaluation Method for the Service Life of Scrapped Copper Wires. (15th July 2021) - Yu, Huiling; Sun, Hao; Liu, Weixia; Zhang, Ruiqiu; Yan, Yurong; Wu, Songping
Abstract: To answer ever‐growing challenges in the copper industry, the recycling of secondary copper resources has aroused much interest. However, an evaluation method for the service life of scrapped copper wires is lacking to date. In this work, a data‐based, multicategorized solution is built to rationally assess evolution law of economic value with time flow for recycled copper‐cored wires, covering their one‐way full cycle including reproduction, storage and sale, and final utilization. Here, the results of reproduced cycles, product life, and service life are logically integrated to establish an inherent relation between engineering and sociology by computer science. Such work provides a multiangle perspective for the value evolution emerging in reproduction/application of waste resources. The basic method originating from the current research is expected to throw light on assessing similar scenes. Abstract : Total life cycle cost assessment, combined with market research facing product life and service life of typical household wires/cables, can be simulated to produce a function establishing the relation between economic value of recycled copper product and its time flow in a one‐way full cycle.